「COVID-19 に対する各大学の対応と生理学及び薬理学教育への影響に関する緊急合同調査」についての結果報告 - 乙黒, 兼一; 古屋敷, 智之; 田熊, 一敞; 田中, 智之; 南, 雅文; 茂木, 正樹 (日本薬理学会年会要旨集, 2021)
COVID-19 pandemic from spring, 2020 changed pharmacological education. To reveal its actual status, the Physiology Society of Japan and the Japanese Pharmacological Society jointly conducted nationwide emergency survey on the response to COVID-19 pandemic and the change of educational environment in universities and colleges from August 26 to September 15, 2020. Here, we demonstrated the results from the Department of Pharmacology in Medical, Dental and Veterinary School. Response rate was high around 90%. How to do the lecture and the practice were changed in 80% and 70%, respectively. Instead of face-to-face teaching, online methods were widely utilized. Live and on-demand streaming used around 30% each and mixed streaming around 40% in the lecture, while live and mixed streaming used around 25% each and on-demand streaming around 45% in the practice. Online methods were also adopted in attendance confirmation and conduct of examination. There are several problems to do online methods such as "unstable network environment", "lack of the reality for students" and "difficulty in the check of their understanding". On the other hand, there are unexpected benefits in online methods such as "anytime and repeatable learning", "an increase in questions from students" and "concentration of learning". 60% of responders insist they will utilize the changed methods in the future. In this part, we would discuss on "new normal" pharmacological education from this survey results.